2004
DOI: 10.1007/bf02980127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polysaccharide ginsan fromPanax ginseng on liver function

Abstract: Ginsan, a polysaccharide isolated from Panax ginseng, has been shown to be a potent immunomodulator, producing a variety of cytokines such as TNF-alpha, IL-1, IL-2, IL-6, IL-12, IFN-gamma and GM-CSF, and stimulating lymphoid cells to proliferate. In the present study, we analyzed some immune functions 1st-5th days after ginsan i.p. injection, including the level of non-protein thiols (NPSH) as antioxidants, heme oxygenase (HO) activity as a marker of oxidative stress, zoxazolamine-induced paralysis time and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The drug metabolism of APG and its effects on liver have been previously examined [19]. Although there appeared to be marginal difference between males and females, APG did not show significant hepatic toxicity, and did not cause any changes in the alanine aminotransferase and aspartate aminotransferease levels.…”
Section: Discussionmentioning
confidence: 99%
“…The drug metabolism of APG and its effects on liver have been previously examined [19]. Although there appeared to be marginal difference between males and females, APG did not show significant hepatic toxicity, and did not cause any changes in the alanine aminotransferase and aspartate aminotransferease levels.…”
Section: Discussionmentioning
confidence: 99%
“…These data illustrated that the antiseptic activity of ginsan against S. aureus can be attributed to the suppression of acute inflammatory responses at an early phase, and enhanced bacterial clearance at subsequent phases of infection. Song et al (2004) analyzed the effects of polysaccharide ginsan from P. ginseng on liver function. The data showed that ginsan treatment did not seem to cause hepatic injury, since serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) activities as well as levels of total bilirubin and albumin were not changed.…”
Section: Anti-septicaemic Activitymentioning
confidence: 99%
“…promoting the maturation, differentiation and reproduction of three kinds of cells (lymphocytes, macrophages and natural killer cells) [13]; simultaneously activating complements and the endothelial system on the endoplasmic reticulum; promoting the generation of a variety of cytokines [14]; and ultimately inhibiting the growth of tumor cells or causing the apoptosis of tumor cells. Other polysaccharides which are being researched further include Bergenia crassifolia pectin polysaccharide [20], Phellinus linteus polysaccharide [21], Grifola frondosa polysaccharide [22], Panax ginseng polysaccharide [23], Agaricus blazei polysaccharide [24], Antrodia cinnamomea polysaccharide [25], lycium barbarum polysaccharide [26], acetobacter polysaccharide [27] and so on [28,29]. Some polysaccharides, like lentinan [15,16], polysaccharide from Ganoderma lucidum [17,18], polysaccharide from Coriolus versicolor [19] and so on have been formally used in clinic and favored by doctors.…”
Section: Antitumor Activitymentioning
confidence: 99%